Contact potential difference of alloy steel after heat treatment - L. P. Aref`eva; A. G. Sukiyazov; Yu. V. Dolgachev; L. S. Shakhova (Advanced Engineering Research, 2020)
Introduction. The paper considers an actual issue of the development and application of a non-destructive method for controlling the quality of surfaces of steel products (Kelvin probe method). The work objective is to establish the magnitude of the contact potential difference (CPD) of steel 107WCR5 after heat treatment.Materials and Methods. The object of study is alloy tool steel 107WCR5. The chemical composition of the samples was refined through the optical emission analysis method. To carry out the statistical processing, there were three samples in three series. We chose different heat treatment modes for each series, i.e., quenching with low tempering, strengthening and normalization. The end surfaces of the samples were polished and then one of them was treated with a solution of nitric acid. Further, the measurement of the contact potential difference and statistical data processing were carried out. Results. The data obtained show that the CPD value of steel 107WCR5 samples changes after heat treatment. With an increase in tempering temperature, the contact potential difference of the polished surface and the hardness, decrease almost linearly. Exposure to acid causes a significant decrease and equalization of the contact potential difference for all structures. The contact potential difference of steels 107WCR5 and CT105 is compared. Alloying steel by the elements with the work function values of the electron higher than that of iron causes a decrease in the CPD between the standard and the sample. The CPD behavior under a change in the composition of the steel depends strongly on the presence of alloying elements. The dependence of CPD on the dispersion of the structure is seen in both cases; however, it is more pronounced for 107WCR5 steel. The electron work function of the martensite, troostite, and sorbitol structures obtained as a result of heat treatment of steels 107WCR5 and CT105 is calculated. Discussion and Conclusions. The dependence of the contact potential difference on the structure, chemical and phase composition was experimentally established; the electron work function of steels 107WCR5 and CT105 was calculated. This technique is more sensitive to alloy steel samples than to carbon steel. It seems possible to conclude that the measurement of the contact potential difference can be used to control surfaces exposed to active media or elevated temperatures as a non-destructive express diagnostic method.